Persamaan linier Tinggi Bukaan Pintu Air Terhadap Kecepatan Aliran dengan Kedalaman Basah di saluran irigasi berbasis IoT Desa Sukoanyar - Soraya Norma; Eko Noerhayati; Bambang Suprapto; Muhammad Rizal A’rofi (Universitas Islam Malang, 2023)
When using floodgates, which can waste water or even cause a shortage if not used properly, it is crucial to pay attention to the regulation of irrigation water. setting up In this study, the Internet of Things (IoT)-based technology can be used to measure when the floodgates open. Farmers that use this technology can better manage water in irrigation systems and planting systems. This study examines the mathematical relationship between the height of irrigation gates based on the Internet of Things and the hydraulics of the flow in the irrigation canals of Sukoanyar Village, Pakis District. Each door opening height has six points, with four points occurring before the door and two points following the door. The size of the sluice gate, the topography of the canal, and the speed of the water flow are the data that were analyzed for this study. The calculation of the channel geometry values comes first in the analysis process, which is followed by the processing of the flow velocity values for each experimental result. The goal of the five experiments conducted at each place was to directly measure the flow velocity using current meter equipment. Using a nonlinear equation mathematical analysis, the study's findings revealed that the height of the irrigation sluice gate (IoT) has an impact on the change in the canal's dynamics value. Keywords: Nonlinear; Irrigation; Internet of Things; Watergates.